The Cost of Free Money - Subacchi, Paola (Ascent Audio, 2020)
A penetrating account of how unchecked capital mobility is damaging international cooperation, polarizing the economic landscape, and ultimately reshaping the global order When it comes to the afflictions of the global economy, almost everyone-and especially Donald Trump-is quick to point the finger of blame at the state of international trade. But what about unconstrained capital flows? Unfettered capital has resulted in a string of financial and economic crises that have left our political systems strained and dialogue corroded. The once perceived benefits of openness have been cast to the wayside and the cracks in the global order can no longer be ignored. Paola Subacchi argues that international cooperation and interdependence have become crippled. Regional restrictions will soon strengthen and a multipolar order will take shape, leading to a distinctly transformed economic landscape in which China challenges the dominance of the US dollar. Combining history, analysis, and prediction, this book provides penetrating insight into the challenges facing the international economic order.